Does the Institutional Quality Affect Labor Productivity in Italian Vineyard Farms? - Maria Raimondo; Concetta Nazzaro; Annamaria Nifo; Giuseppe Marotta (Wine Economics and Policy)
The paper aims at analyzing the effect of institutional quality on labor productivity in the agricultural sector. To meet this aim, a Gaussian log-linear model was applied to 773 vineyard farms, located in 71 Italian provinces. The applied methodology enabled to quantify the overall impact of the institutional quality on labor productivity by discriminating with respect to the Italian regions and macro-areas (i.e. North, South or Central Italy). The findings of the investigation show a positive effect of the institutional quality on labor productivity, with an overall impact of 39%. Moreover, huge differences among Italian regions and macro-areas were detected. The study findings provide recommendations for academics and policy-makers to improve both theoretical and practical aspects.